Grounded Theory and Autopoietic Social Systems: Are They Methodologically Compatible? - Mitchell, Richard C. (Qualitative Sociology Review, 2007)
The paper offers a secondary analysis from a grounded theory doctoral study that reconsiders its “grounded systemic design” (Mitchell, 2005, 2007). While theorists across multiple disciplines fiercely debate the ontological implications of Niklas Luhmann’s autopoietic systems theory (Deflem 1998; Graber and Teubner 1998; King and Thornhill 2003; Mingers 2002; Neves 2001; O’Byrne 2003; Verschraegen 2002, for example), few investigators have yet to adopt his core constructs empirically (see Gregory, Gibson and Robinson 2005 for an exception). Glaser’s (1992, 2005) repeated concerns for grounded theorists to elucidate a “theoretical code” has provided an additional entry point into this project of integrating grounded theory with Luhmann’s abstract conceptual thinking about how global society operates. The author argues that this integration of methodology and systems thinking provides an evolution of grounded theory – rather than its ongoing “erosion” as Greckhamer and Koro-Ljungberg (2005) have feared – and a transportable set of methodological and analytical constructs is presented as a basis for further grounded study.